Sound Generation By Flow Over Multiple Shallow Cavities - Shaaban, Ayman (My University, 2018)
Corrugated pipes are widely used in offshore gas and oil fields for their flexibility while offering local rigidity. However, self-sustained pressure pulsations associated with the flow in corrugated pipes results in a noisy environment, high running costs and eventually structure fatigue failure upon long exposure. Recent literature has addressed either the flow over a single cavity or the global oscillations. The current research aims at understanding the flow over multiple cavities as a first step to correlate the rich single cavity literature and the actual corrugated pipe problem with the ultimate goal of predicting oscillations amplitude in corrugate pipes. The standing wave method (SWM), which is an efficient experimental tool, has been successfully adapted in the first phase of the project to measure the source of multiple cavity configurations. One, two and three-cavity configurations have been investigated by means of the SWM. The source non-linearly becomes more pronounced as the number of cavities increases. The cavity length (L) is still found to be the appropriate length scale to define the oscillation dimensionless frequency (the Strouhal number). The measured source data have been successfully employed in a semi-empirical model to predict the amplitude of the self-excited oscillations. Accurate model performance is achieved for the single, double and triple cavity configurations. Including the absorption losses at the cavity corners has been found to be crucial for the model prediction accuracy. The separation distance (Lp) effect on the generated source is investigated for two and three-cavity configurations using the SWM over a practical range of spacing ratios. At extremum spacing ratios of (Lp/L) 0.5 and 1.375, constructive hydrodynamic interference associated with strong sources has been observed. At high excitation levels the source consistently becomes weaker upon increasing the spacing ratio. The reported trends are consistent for both the double and triple cavity configurations. However, the destructive interference spacing ratio is found to depend on the number of cavities indicating a relatively more complicated interaction mechanism. The different interaction patterns have been analytically interpreted based on the synchronization of the hydrodynamic cycle of the cavity shear layer and the disturbance convection along the pipe spacing between the cavities. Moreover, the three-cavity constructive interference cases have been visualized using Particle Image Velocimetry (PIV). The source evaluated based on the PIV data and applying Howe’s analogy revealed each cavity share of the global source, which fairly agrees with the SWM measured source. The source contribution due to gradually increasing the number of cavities is investigated using the SWM up to a six-cavity configuration. The source contribution reaches asymptotically a consistent value starting from the fourth cavity. This persistent contribution defines a building unit cavity source which is representative of a general cavity in a long corrugated pipe. The building unit source fairly agrees with the ninth-cavity source in a twelve-cavity configuration extracted by means of the PIV technique. Finally, a predication model, based on the building unit source, successfully predicts the oscillations amplitude of a twelve-cavity configuration, which serves as a model for a corrugated pipe section.
Keywords: multiple cavities; corrugated pipes; aeroacoustic source; fluid-structure interaction; flow-sound interaction; PIV